Parenting at three generations of Oei Family in “Oei Hui Lan” biography - Halim, Steffi Thanissa; Ardiyanto, Grace Febriana (Universitas Dian Nuswantoro, 2024)
Oei Hui Lan family was the richest family in Southeast Asia until 20th century, and belongs to the Chinese elite group, so they also have good connection with the western people which made Oei family’s parenting style different from other ordinary Chinese Indonesian families at their time. This makes the author interested in researching parenting styles in three generations of Oei family. The author uses library research method, namely the content analysis method to analyze the data. The data is taken from